â€œBlack Goldâ€: Environmental Degradation and Social Marginalization - Siburian, Robert (Jurnal Penelitian Kesejahteraan Sosial, 2018)
This paper explains that coal mining as a heavy industry does not bring the expected prosperity to the community. At the macro level, the activity of mining gives a significant contribution to national economy, including provide job opportunities. But at the micro level, enviromental degradation seems dominant with its impact to the environment. The impact is the process of marginalize for local people, especially for some people who live on agricultural sector. The degradation to the environment makes the capacity of agricultural lands becoming low in production whereas the access of farmers to the fertile lands and other economical resources are very limited. The condition is getting complex when at the same time there are many newcomers from other areas searching for better life so it has caused the environmental degradation worser. The existence of the newcomers has made the competition among the people there to get land and economical resource is getting high. This competition will make the local people or farmers becoming marginalized because they could not compete in the situation and they lose many opportunities. Those phenomena happens due to the politics of ecology played by national and local goverments through policies which only focus on the economy sector.